Cardiovascular mortality after pre-eclampsia in one child mothers: prospective, population based cohort study. (27th November 2012) - Skjaerven, Rolv; Wilcox, Allen J; Klungsøyr, Kari; Irgens, Lorentz M; Vikse, Bjørn Egil; Vatten, Lars J; Lie, Rolv Terje
Abstract : Objective To assess the association of pre-eclampsia with later cardiovascular death in mothers according to their lifetime number of pregnancies, and particularly after only one child. Design Prospective, population based cohort study. Setting Medical Birth Registry of Norway. Participants We followed 836 147 Norwegian women with a first singleton birth between 1967 and 2002 for cardiovascular mortality through linkage to the national Cause of Death Registry. About 23 000 women died by 2009, of whom 3891 died from cardiovascular causes. Associations between pre-eclampsia and cardiovascular death were assessed by hazard ratios, estimated by Cox regression analyses. Hazard ratios were adjusted for maternal education (three categories), maternal age at first birth, and year of first birth Results The rate of cardiovascular mortality among women with preterm pre-eclampsia was 9.2% after having only one child, falling to 1.1% for those with two or more children. With term pre-eclampsia, the rates were 2.8% and 1.1%, respectively. Women with pre-eclampsia in their first pregnancy had higher rates of cardiovascular death than those who did not have the condition at first birth (adjusted hazard ratio 1.6 (95% confidence interval 1.4 to 2.0) after term pre-eclampsia; 3.7 (2.7 to 4.8) after preterm pre-eclampsia). Among women with only one lifetime pregnancy, the increase in risk of cardiovascular death was higher than for those with two or more children (3.4 (2.6 to 4.6) after term pre-eclampsia; 9.4 (6.5 to 13.7) after preterm pre-eclampsia). The risk of cardiovascular death was only moderately elevated among women with pre-eclamptic first pregnancies who went on to have additional children (1.5 (1.2 to 2.0) after term pre-eclampsia; 2.4 (1.5 to 3.9) after preterm pre-eclampsia). There was little evidence of additional risk after recurrent pre-eclampsia. All cause mortality for women with two or more lifetime births, who had pre-eclampsia in first pregnancy, was not elevated, even with preterm pre-eclampsia in first pregnancy (1.1 (0.87 to 1.14)). Conclusions Cardiovascular death in women with pre-eclampsia in their first pregnancy is concentrated mainly in women with no additional births. This association might be due to health problems that discourage or prevent further pregnancies rather than to pre-eclampsia itself. As a screening criterion for cardiovascular disease risk, pre-eclampsia is a strong predictor primarily among women with only one child—particularly with preterm pre-eclampsia.